Migration direction in a songbird explained by two loci - Kristaps Sokolovskis; Max Lundberg; Susanne Åkesson; Mikkel Willemoes; Tianhao Zhao; Violeta Caballero-Lopez; Staffan Bensch (Nature Communications, 2023)
The genetic determinants of long-distance migration in birds are largely unknown. Sokolovskis et al. tracked genotyped hybrid willow warblers from a migratory divide in Sweden and find that autumn migration direction is consistent with a dominant inheritance pattern of two large effect loci that interact through epistasis.